EFFECT OF TASK SPECIFIC MIRROR THERAPY WITH FUNCTIONAL ELECTRICAL STIMULATION ON UPPER LIMB FUNCTION FOR SUBACUTE HEMIPLEGIA (International Journal of Physiotherapy, 2015)
Background: The principal target of any stroke rehabilitation is the motor impairments. Many studies have been advocated on the effect of Functional electrical stimulation and Task specific mirror therapy. Hence, the purpose of the study is to find the combined effect of task specific Mirror therapy with Functional Electrical Stimulation on upper limb function for subjects with sub-acute hemiplegia.Methods: An experimental study design, 60 subjects with sub-acute Hemiplegia randomised into 3 groups, functional electrical stimulation group (n=20), task specific mirror therapy group (n=20), and combined group (n=20). Each group received the corresponding regimen of treatment for 30 minutes with rest period for total 12 sessions over 2 weeks along with conventional physiotherapy. The outcome measure such as action research arm test was measured before and after two weeks of intervention.Result: When means of action research arm test were analyzed within the groups, there was a significant difference within all the three groups. When means were compared between three groups there is no statistically significant difference in pre- intervention and post intervention means.Conclusion: It is concluded that a combination therapy of task specific mirror therapy with functional electrical stimulation for two weeks duration, is shown to be effective for recovery of upper limb function in subjects with sub-acute hemiplegia. However, the combination of task specific mirror therapy and functional electrical stimulation is shown to have similar improvements as only task specific mirror therapy and functional electrical stimulation.